Establishing the UiTM-MERCY Resilient Community Centre: fostering resilience and community engagement - Ismail, Dzulkarnaen; Ab Samah, Norazam; Syed Mustapa, Syed Abdul Haris; Ab Gani, Muhamad Abdul Aziz (Universiti Teknologi MARA, Kedah, 2024)
This proposal outlines the establishment of a UiTM-MERCY Resilient Community Centre at Universiti Teknologi MARA (UiTM) Seri Iskandar, Perak. The collaboration between UiTM and MERCY Malaysia seeks to enhance community well-being and preparedness by establishing a comprehensive hub for resilience-building activities. This centre aims to provide essential resources, training, and support to the local community, fostering a culture of preparedness and adaptive capacity in the face of potential disasters and challenges. The primary objectives of the centre are to improve the overall resilience of the community by providing access to resources, training, and information. The centre will facilitate community-led initiatives, promote health and safety practices, and offer support during emergencies. Additionally, it will serve as a platform for research and collaboration between academia, local authorities, and community members. The proposal draws upon a comprehensive review of previous activities and successful models in similar settings, including disaster preparedness workshops, health campaigns, and community outreach programs. The centre will leverage these experiences to design a wide range of services and activities tailored to the local context. Key activities will include resilience training, mental health support, environmental sustainability projects, and emergency response simulations. The establishment of the Resilient Community Centre is expected to result in a well-informed and empowered community capable of responding effectively to various challenges. It aims to build a network of resilient individuals and groups, fostering a collaborative environment for continuous learning and improvement. The centre will not only enhance the immediate preparedness and response capacity of the community but also contribute to long-term sustainable development goals.